Alkaline-free glass plate

JP7644405B2Active Publication Date: 2025-03-12NIPPON ELECTRIC GLASS CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2020105253
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-06-18
Publication Date
2025-03-12
Estimated Expiration
2040-06-18

Smart Images

  • Figure 0007644405000001
    Figure 0007644405000001
Patent Text Reader

Abstract

To provide an alkali-free glass plate that has excellent productivity and sufficiently high strain point and Young's modulus.SOLUTION: The alkali-free glass plate of the present invention is characterized in that a contained amount of Li2O+Na2O+K2O in a glass composition is 0 to 0.5 mol%, Young's modulus is 80 GPa or more, a strain point is 700°C or more, and a liquid phase temperature is 1350°C or lower.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an alkali-free glass plate, and more particularly to an alkali-free glass plate suitable for an organic EL display. [Background technology]

[0002] Electronic devices such as organic electroluminescence (EL) displays are thin, have excellent moving image display capabilities, and consume low power, so they are used in applications such as flexible devices and mobile phone displays.

[0003] Glass plates are widely used as substrates for organic electroluminescence displays. Glass plates for this purpose are required to have the following characteristics: (1) In order to prevent alkali ions from diffusing into the semiconductor material formed in the heat treatment process, the glass contains almost no alkali metal oxides, i.e., it is an alkali-free glass (the content of alkali oxides in the glass composition is 0.5 mol% or less). (2) To reduce the cost of glass sheets, the glass must be highly productive, particularly in terms of melting property and resistance to devitrification. (3) A high strain point is required to reduce thermal shrinkage of glass plates in the LTPS (low temperature polysilicon) process and oxide TFT process. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2012-106919 A DISCLOSURE OF THEINVENTION [Problem to be solved by the invention]

[0005] Meanwhile, organic EL devices are also widely used in organic EL televisions. There is a strong demand for organic EL televisions to be larger and thinner, and the demand for high-resolution displays such as 8K is increasing. Therefore, glass sheets for these applications are required to have thermal dimensional stability that can withstand the demand for high resolution while being larger and thinner. Furthermore, in order to reduce the price difference with liquid crystal displays, further cost reduction is required, and glass sheets are also required to be low cost. However, when glass sheets are made larger and thinner, they become more prone to bending, which causes the manufacturing cost to rise.

[0006] Glass sheets formed by glass manufacturers go through processes such as cutting, annealing, inspection, and cleaning, and during these processes, the glass sheets are loaded into and removed from a cassette with multiple shelves. This cassette is usually designed so that the opposing sides of the glass sheet can be placed on shelves formed on the left and right inner sides and held in a horizontal direction. However, large and thin glass sheets have a large amount of deflection, so that when the glass sheet is loaded into the cassette, a part of the glass sheet comes into contact with the cassette and is broken, and when the glass sheet is removed, it is likely to swing significantly and become unstable. Cassettes of this type are also used by electronic device manufacturers, so similar problems will occur. In order to solve this problem, a method of increasing the Young's modulus of the glass sheet and reducing the amount of deflection is effective.

[0007] Furthermore, as described above, in the LTPS or oxide TFT process for obtaining a high-resolution display, it is necessary to increase the strain point of the glass plate in order to reduce the thermal shrinkage of the large glass plate.

[0008] However, if the Young's modulus and strain point of the glass plate are increased, the balance of the glass composition is lost, the productivity is reduced, and in particular, the devitrification resistance is likely to be significantly reduced. In addition, the melting property is reduced, and the forming temperature of the glass is increased, which is likely to shorten the life of the formed body. As a result, the cost of the original glass plate is increased.

[0009] The present invention has been made in view of the above circumstances, and its technical object is to provide an alkali-free glass sheet which is excellent in productivity and has a sufficiently high strain point and Young's modulus. [Means for solving the problem]

[0010] As a result of repeated various experiments, the present inventors have found that the above technical problems can be solved by strictly controlling the glass properties of the alkali-free glass plate, and propose this as the present invention. That is, the alkali-free glass plate of the present invention is characterized in that the content of Li2O+Na2O+K2O in the glass composition is 0 to 0.5 mol%, the Young's modulus is 80 GPa or more, the strain point is 700°C or more, and the liquidus temperature is 1350°C or less. Here, "Li2O+Na2O+K2O" refers to the total amount of Li2O, Na2O, and K2O. "Young's modulus" refers to a value measured by a bending resonance method. Note that 1 GPa is approximately 101.9 Kgf / mm 2 "Strain point" refers to a value measured based on the method of ASTM C336. "Liquidus temperature" refers to the temperature at which crystals precipitate when a glass powder that passes through a standard sieve of 30 mesh (500 μm) and remains on a 50 mesh (300 μm) is placed in a platinum boat and held in a temperature gradient furnace for 24 hours.

[0011] The alkali-free glass plate of the present invention has a glass composition containing, in mol%, 64-71% SiO2, 12-17% Al2O3, 0-5% B2O3, 0-0.5% Li2O+Na2O+K2O, 5-9% MgO, 2-10% CaO, 0-7% SrO, more than 1-7% BaO, and 14-20% MgO+CaO+SrO+BaO, and is characterized in that the molar ratio of Al2O3 / BaO is 1.8-10, the molar ratio of B2O3 / (MgO+CaO+SrO+BaO) is 0-0.2, the molar ratio of (B2O3+MgO) / SiO2 is 0.1-0.2, and the molar ratio of B2O3 / MgO is 0-0.5. Here, "MgO+CaO+SrO+BaO" refers to the combined amount of MgO, CaO, SrO, and BaO. "Al2O3 / BaO" refers to the value obtained by dividing the Al2O3 content by the BaO content. "B2O3 / (MgO+CaO+SrO+BaO)" refers to the value obtained by dividing the B2O3 content by the combined amount of MgO, CaO, SrO, and BaO. "(B2O3+MgO) / SiO2" refers to the value obtained by dividing the combined amount of B2O3 and MgO by the SiO2 content. "B2O3 / MgO" refers to the value obtained by dividing the B2O3 content by the MgO content.

[0012] The alkali-free glass plate of the present invention preferably further contains substantially no As2O3 and no Sb2O3. Here, "substantially no As2O3 and no Sb2O3" refers to the case where the contents of As2O3 and Sb2O3 in the glass composition are each less than 0.05%.

[0013] Moreover, the alkali-free glass plate of the present invention preferably further contains 0.001 to 1 mol % of SnO2.

[0014] The alkali-free glass plate of the present invention preferably has a strain point of 710° C. or higher.

[0015] The alkali-free glass plate of the present invention preferably has a Young's modulus of more than 81 GPa.

[0016] In addition, the alkali-free glass plate of the present invention has an average thermal expansion coefficient of 30×10 in a temperature range of 30 to 380° C. -7~50×10 -7 / ° C. Here, the "average thermal expansion coefficient in the temperature range of 30 to 380° C." can be measured by a dilatometer.

[0017] In addition, the alkali-free glass sheet of the present invention has a liquidus viscosity of 10 4.0 It is preferable that the viscosity is dPa·s or more. Here, the "liquidus viscosity" refers to the viscosity of glass at the liquidus temperature, and can be measured by the platinum sphere pull-up method.

[0018] The alkali-free glass plate of the present invention is preferably used in an organic EL device. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] The alkali-free glass plate of the present invention is characterized in that, as a glass composition, it contains, in mol%, SiO2 64-71%, Al2O3 12-17%, B2O3 0-5%, Li2O+Na2O+K2O 0-0.5%, MgO 5-9%, CaO 2-10%, SrO 0-7%, BaO more than 1-7%, MgO+CaO+SrO+BaO 14-20%, and the molar ratio Al2O3 / BaO is 1.8-10, the molar ratio B2O3 / (MgO+CaO+SrO+BaO) is 0-0.2, the molar ratio (B2O3+MgO) / SiO2 is 0.1-0.2, and the molar ratio B2O3 / MgO is 0-0.5. The reasons for limiting the content of each component as described above are as follows. In the explanation of the content of each component, % indicates mol % unless otherwise specified.

[0020] SiO2 is a component that forms the skeleton of glass. If the content of SiO2 is too low, the thermal expansion coefficient increases and the density increases. Therefore, the lower limit of SiO2 is preferably 64%, more preferably 64.2%, more preferably 64.4%, more preferably 64.6%, more preferably 64.8%, more preferably 65%, and most preferably 65.2%. On the other hand, if the content of SiO2 is too high, the Young's modulus decreases, the high-temperature viscosity increases, the amount of heat required during melting increases, the melting cost increases, and defects occur due to the remaining SiO2 raw material, which may cause a decrease in yield. In addition, devitrified crystals such as cristobalite are likely to precipitate, and the liquidus viscosity is likely to decrease. Therefore, the upper limit of SiO2 is preferably 71%, more preferably 70.8%, more preferably 70.6%, more preferably 71.4%, more preferably 70.2%, more preferably 70%, and most preferably 69.8%.

[0021] Al2O3 is a component that forms the skeleton of glass, increases the Young's modulus, and increases the strain point. If the content of Al2O3 is too low, the Young's modulus and the strain point tend to decrease. Therefore, the lower limit of Al2O3 is preferably 12%, more preferably more than 12%, more preferably 12.1%, more preferably 12.2%, more preferably 12.5%, more preferably 12.6%, more preferably 12.8%, and most preferably 13%. On the other hand, if the content of Al2O3 is too high, devitrified crystals such as mullite tend to precipitate and the liquidus viscosity tends to decrease. Therefore, the upper limit of Al2O3 is preferably 17%, more preferably 16.8%, more preferably 16.6%, more preferably 16.4%, more preferably 16.2%, and most preferably 16%.

[0022] B2O3 is a component that enhances meltability and devitrification resistance. If the content of B2O3 is too low, the meltability and devitrification resistance are likely to decrease. Therefore, the lower limit of B2O3 is preferably 0%, more preferably more than 0%, more preferably 0.1%, even more preferably 0.2%, even more preferably 0.3%, even more preferably 0.4%, and most preferably more than 1%. On the other hand, if the content of B2O3 is too high, the Young's modulus and strain point are likely to decrease. Therefore, the upper limit of B2O3 is preferably 5%, more preferably 4.8%, more preferably 4.6%, even more preferably 4.4%, even more preferably 4.2%, and most preferably 4%.

[0023] Li2O, Na2O and K2O are components that are inevitably mixed in from the glass raw materials, and the total amount thereof is preferably 0 to 0.5%, more preferably 0 to 0.3%, and most preferably 0 to 0.2%. If the total amount of Li2O, Na2O and K2O is too large, there is a risk that alkali ions will diffuse into the semiconductor material formed in the film in the heat treatment step.

[0024] Among alkaline earth metal oxides, MgO is a component that significantly increases the Young's modulus. If the content of MgO is too low, the melting property and Young's modulus are likely to decrease. Therefore, the lower limit of MgO is preferably 5%, more preferably 5.1%, more preferably 5.2%, even more preferably 5.3%, even more preferably 5.4%, even more preferably 5.5%, even more preferably 5.6%, and most preferably 5.7%. On the other hand, if the content of MgO is too high, devitrified crystals such as mullite are likely to precipitate, and the liquidus viscosity is likely to decrease. Therefore, the upper limit of MgO is preferably 9%, more preferably 8.9%, more preferably 8.8%, more preferably 8.7%, even more preferably 8.6%, even more preferably 8.5%, even more preferably less than 8.5%, even more preferably 8.4%, and most preferably less than 8.4%.

[0025] CaO is a component that reduces high-temperature viscosity without lowering the strain point and significantly increases meltability. It is also a component that increases Young's modulus. If the CaO content is too small, it becomes difficult to enjoy the above effects, and meltability is likely to decrease. Furthermore, devitrification resistance is likely to decrease. Therefore, the lower limit of CaO is preferably 2%, more preferably 2.2%, more preferably 2.4%, even more preferably 2.5%, even more preferably 2.6%, even more preferably 2.8%, even more preferably 3%, and most preferably more than 3%. On the other hand, if the CaO content is too high, the liquidus temperature becomes high. Therefore, the upper limit of CaO is preferably 10%, more preferably 9.9%, more preferably 9.8%, even more preferably 9.7%, even more preferably 9.6%, even more preferably 9.5%, even more preferably 9.4%, even more preferably 9.3%, and most preferably 9.2%.

[0026] SrO is a component that enhances devitrification resistance, and furthermore, it is a component that reduces high-temperature viscosity and enhances melting property without lowering the strain point. It is also a component that suppresses the decrease in liquidus viscosity. If the content of SrO is too small, it is difficult to enjoy the above effects. Therefore, the lower limit of SrO is preferably 0%, more preferably more than 0%, more preferably 0.1%, more preferably more than 0.1%, more preferably 0.2%, more preferably 0.3%, more preferably more than 0.3%, more preferably 0.4%, and most preferably more than 0.4%. On the other hand, if the content of SrO is too high, the thermal expansion coefficient and density tend to increase. Therefore, the upper limit of SrO is preferably 6%, more preferably less than 6%, more preferably 5.9%, more preferably less than 5.9%, more preferably 5.8%, more preferably less than 5.8%, more preferably 5.7%, more preferably less than 5%, more preferably 4%, and most preferably 3%.

[0027] BaO is a component that enhances devitrification resistance. If the content of BaO is too low, it is difficult to enjoy the above effects. Therefore, the lower limit of BaO is preferably more than 1%, more preferably 1.1%, more preferably 1.2%, even more preferably 1.3%, even more preferably 1.4%, even more preferably 1.5%, even more preferably 1.6%, and most preferably 1.7%. On the other hand, if the content of BaO is too high, the Young's modulus is likely to decrease, and the thermal expansion coefficient and density are likely to increase. Therefore, the upper limit of BaO is preferably 7%, more preferably 6.8%, more preferably 6.6%, even more preferably 6.4%, even more preferably 6.2%, even more preferably 6%, and most preferably less than 6%.

[0028] If the total amount of MgO, CaO, SrO and BaO is too large or too small, the melting property is likely to be deteriorated. If the total amount of MgO, CaO, SrO and BaO is too small, the melting property is likely to be reduced, and the Young's modulus is also likely to be reduced. Therefore, the lower limit of the total amount of MgO, CaO, SrO and BaO is preferably 14%, more preferably 14.5%, more preferably 15%, even more preferably 15.3%, even more preferably 15.5%, even more preferably 15.8%, even more preferably 15.9%, and most preferably 16%. On the other hand, if the total amount of MgO, CaO, SrO and BaO is too large, the thermal expansion coefficient and density are likely to increase. Therefore, the upper limit of the total amount of MgO, CaO, SrO and BaO is preferably 20%, more preferably 19.8%, more preferably 19.6%, even more preferably 19.4%, even more preferably 19.2%, even more preferably 19%, and most preferably less than 19%.

[0029] If the molar ratio Al2O3 / BaO is too small, the Young's modulus is likely to decrease. Therefore, the lower limit of Al2O3 / BaO is preferably 1.8, more preferably 2, more preferably 3, even more preferably 4, even more preferably 4.5, and most preferably 5. If the Al2O3 / BaO is too large, the liquidus viscosity is likely to decrease. Therefore, the upper limit of Al2O3 / BaO is preferably 10, more preferably 9.8, more preferably 9.6, even more preferably 9.4, even more preferably 9.2, and most preferably 9.

[0030] If the molar ratio B2O3 / (MgO+CaO+SrO+BaO) is too small, the melting property is likely to decrease. Therefore, the lower limit of B2O3 / (MgO+CaO+SrO+BaO) is preferably 0, more preferably more than 0, more preferably 0.01, even more preferably 0.02, even more preferably 0.03, and most preferably 0.04. If B2O3 / (MgO+CaO+SrO+BaO) is too large, the strain point is likely to decrease. Therefore, the upper limit of B2O3 / (MgO+CaO+SrO+BaO) is preferably 0.2, more preferably 0.19, more preferably 0.18, even more preferably 0.17, even more preferably 0.16, and most preferably 0.15.

[0031] If the molar ratio (B2O3+MgO) / SiO2 is too small, the melting property is likely to decrease. Therefore, the lower limit of (B2O3+MgO) / SiO2 is preferably 0.1, more preferably more than 0.1, more preferably 0.11, even more preferably 0.12, even more preferably 0.13, and most preferably 0.14. If (B2O3+MgO) / SiO2 is too large, the strain point is likely to decrease. Therefore, the upper limit of (B2O3+MgO) / SiO2 is preferably 0.2, more preferably less than 0.2, more preferably 0.19, even more preferably 0.18, even more preferably 0.17, and most preferably 0.16.

[0032] The molar ratio B2O3 / MgO is an important component ratio for achieving both high Young's modulus, high melting property, low thermal shrinkage, and productivity. If B2O3 / MgO is too small, the liquidus temperature will be high, leading to a decrease in productivity, or melting property will be easily decreased, or the molding temperature will be high, leading to a shortened life of the molded body, leading to an increase in the cost of the glass. Therefore, the lower limit of B2O3 / MgO is preferably 0, more preferably more than 0, more preferably 0.03, even more preferably 0.05, even more preferably 0.08, and most preferably 0.1. If B2O3 / MgO is too large, the strain point will be lowered, making it impossible to obtain high thermal dimensional stability, or the Young's modulus will be lowered, leading to a large glass plate being easily warped. Therefore, the upper limit of B2O3 / MgO is preferably 0.5, more preferably 0.48, more preferably 0.46, even more preferably 0.44, even more preferably 0.42, even more preferably 0.40, even more preferably 0.37, even more preferably 0.36, even more preferably 0.35, even more preferably 0.33, and most preferably 0.30.

[0033] In addition to the above components, the following components may be added as optional components. From the viewpoint of accurately enjoying the effects of the present invention, the content of the components other than the above components is preferably 10% or less in total, and particularly preferably 5% or less.

[0034] P2O5 is a component that increases the strain point and can significantly suppress the precipitation of devitrified crystals of alkaline earth aluminosilicates such as anorthite. However, if a large amount of P2O5 is contained, the glass is more likely to undergo phase separation. The content of P2O5 is preferably 0 to 2.5%, more preferably 0.0005 to 1.5%, further preferably 0.001 to 0.5%, and particularly preferably 0.005 to 0.3%.

[0035] TiO2 is a component that reduces high-temperature viscosity and enhances melting property, and also suppresses solarization, but if TiO2 is contained in a large amount, the glass becomes colored and the transmittance is likely to decrease. The content of TiO2 is preferably 0 to 2.5%, more preferably 0.0005 to 1%, further preferably 0.001 to 0.5%, and particularly preferably 0.005 to 0.1%.

[0036] ZnO is a component that enhances meltability. However, if a large amount of ZnO is contained, the glass is likely to devitrify and the strain point is likely to decrease. The ZnO content is preferably 0 to 6%, 0 to 5%, 0 to 4%, and particularly preferably 0 to less than 3%.

[0037] Y2O3, Nb2O5, and La2O3 have the effect of increasing the strain point, Young's modulus, etc. The total amount and individual content of these components is preferably 0 to 5%, more preferably 0 to 1%, and further preferably 0 to 0.5%. If the total amount and individual content of Y2O3, Nb2O5, and La2O3 are too high, the density and raw material costs are likely to increase.

[0038] SnO2 is a component that has a good clarifying effect in the high temperature range, and also increases the strain point and reduces the high temperature viscosity. The content of SnO2 is preferably 0 to 1%, 0.001 to 1%, 0.01 to 0.5%, and particularly preferably 0.05 to 0.3%. If the content of SnO2 is too high, devitrified crystals of SnO2 are likely to precipitate. If the content of SnO2 is less than 0.001%, it is difficult to enjoy the above effects.

[0039] As described above, SnO2 is suitable as a fining agent, but as long as the glass properties are not impaired, F, SO3, C, or metal powders such as Al and Si can be added as a fining agent up to 5% (preferably up to 1%, particularly up to 0.5%) instead of SnO2 or together with SnO2. CeO2 and the like can also be added as a fining agent up to 5% (preferably up to 1%, particularly up to 0.5%).

[0040] As a fining agent, As2O3 and Sb2O3 are also effective. However, the alkali-free glass plate of the present invention does not substantially contain these components from an environmental viewpoint. Furthermore, if As2O3 is contained, the solarization resistance tends to decrease.

[0041] Cl is a component that promotes the initial melting of a glass batch. In addition, the addition of Cl can promote the action of a fining agent. As a result, the melting cost can be reduced while the life of a glass manufacturing furnace can be extended. However, if the Cl content is too high, the strain point is likely to decrease. Therefore, the Cl content is preferably 0 to 3%, more preferably 0.0005 to 1%, and particularly preferably 0.001 to 0.5%. In addition, as a raw material for introducing Cl, a chloride of an alkaline earth metal oxide such as strontium chloride, or a raw material such as aluminum chloride can be used.

[0042] Fe2O3 is a component that is mixed in as a raw material impurity and reduces electrical resistivity. The content of Fe2O3 is preferably 0 to 300 mass ppm, 80 to 250 mass ppm, and particularly 100 to 200 mass ppm. If the content of Fe2O3 is too low, the raw material cost is likely to rise. On the other hand, if the content of Fe2O3 is too high, the electrical resistivity of the molten glass increases, making it difficult to perform electric melting.

[0043] Particularly preferred glass composition ranges, in mol%, are SiO2 65-70%, Al2O3 12.5-16%, B2O3 0-4%, Li2O+Na2O+K2O 0-0.5%, MgO 5.7-9%, CaO 3-10%, SrO 0-6%, BaO 1-6%, MgO+CaO+SrO+BaO 16-19%, with a molar ratio of Al2O3 / BaO of 2-9, a molar ratio of B2O3 / (MgO+CaO+SrO+BaO) of 0-0.15, a molar ratio of (B2O3+MgO) / SiO2 of 0.1-0.2, and a molar ratio of B2O3 / MgO of 0.1-0.36. This allows productivity to be improved while ensuring a high Young's modulus, high strain point, and high heat resistance (high thermal dimensional stability).

[0044] The alkali-free glass plate of the present invention preferably has the following properties.

[0045] The average thermal expansion coefficient in the temperature range of 30 to 380°C is preferably 30×10 -7 ~50×10 -7 / ℃, 32×10 -7 ~48×10 -7 / ℃, 33×10 -7 ~45×10 -7 / ℃, 34×10 -7 ~44×10 -7 / ℃, especially 35×10 -7 ~43×10 -7 / ° C. This makes it easier to match the thermal expansion coefficient of the Si used in the TFT.

[0046] The Young's modulus is 80 GPa or more, preferably more than 80 GPa, 81 GPa or more, 81 GPa or more, 82 GPa or more, 83 GPa or more, or 84 GPa or more, particularly more than 84 to 95 GPa. If the Young's modulus is too low, defects due to bending of the glass sheet are likely to occur.

[0047] The strain point is 700° C. or higher, preferably more than 700° C., 705° C. or higher, and particularly preferably 710 to 770° C. In this way, the thermal shrinkage of the glass sheet can be suppressed in the LTPS process.

[0048] The liquidus temperature is 1350°C or lower, preferably less than 1350°C, 1300°C or lower, particularly 800 to 1280°C. This makes it easier to prevent the occurrence of devitrification crystals during glass production, which reduces productivity. Furthermore, since it becomes easier to form the glass by the overflow downdraw method, it becomes easier to improve the surface quality of the glass sheet and reduce the manufacturing cost of the glass sheet. The liquidus temperature is an index of devitrification resistance, and the lower the liquidus temperature, the better the devitrification resistance.

[0049] The liquidus viscosity is preferably 10 4.0 dPa s or more, 10 4.1 dPa s or more, 10 4.2 dPa s or more, especially 10 4.3In this way, devitrification is less likely to occur during forming, making it easier to form using the overflow downdraw method, and as a result, it is possible to improve the surface quality of the glass sheet and reduce the manufacturing costs of the glass sheet. The liquidus viscosity is an index of devitrification resistance and formability, and the higher the liquidus viscosity, the better the devitrification resistance and formability.

[0050] High temperature viscosity 10 2.5 The temperature in dPa·s is preferably 1650° C. or less, 1630° C. or less, 1610° C. or less, in particular 1600° C. or less. 2.5 If the temperature at dPa·s is too high, it becomes difficult to melt the glass batch, and the manufacturing cost of glass sheets increases. 2.5 The temperature in dPa·s corresponds to the melting temperature, and the lower this temperature, the better the melting property.

[0051] β-OH is an index showing the amount of water in glass, and by decreasing β-OH, the strain point can be increased. Even if the glass composition is the same, the smaller the β-OH, the smaller the thermal shrinkage at a temperature below the strain point. β-OH is preferably 0.35 / mm or less, 0.30 / mm or less, 0.28 / mm or less, 0.25 / mm or less, and particularly 0.20 / mm or less. If β-OH is too small, the melting property is likely to decrease. Therefore, β-OH is preferably 0.01 / mm or more, and particularly 0.03 / mm or more.

[0052] The following methods can be used to reduce β-OH: (1) Select raw materials with low water content. (2) Add components (Cl, SO3, etc.) to the glass that reduce β-OH. (3) Reduce the water content in the furnace atmosphere. (4) Bubble N2 in the molten glass. (5) Use a small melting furnace. (6) Increase the flow rate of molten glass. (7) Use an electric melting method.

[0053] Here, "β-OH" refers to a value obtained by measuring the transmittance of glass using FT-IR and using the following mathematical formula 1.

[0054] [Number 1] β-OH=(1 / X)log(T1 / T2) X: Plate thickness (mm) T1: Reference wavelength 3846cm -1 Transmittance (%) T2: Hydroxyl group absorption wavelength 3600cm -1 Minimum transmittance (%) near

[0055] The alkali-free glass sheet of the present invention is preferably formed by the overflow down-draw method. The overflow down-draw method is a method for producing a glass sheet by overflowing molten glass from both sides of a heat-resistant trough-shaped structure, and drawing the overflowed molten glass downward while joining at the lower end of the trough-shaped structure. In the overflow down-draw method, the surface to be the surface of the glass sheet is not in contact with the trough-shaped refractory and is formed in a free surface state. Therefore, an unpolished glass sheet with good surface quality can be produced at low cost, and it is easy to make the glass sheet thin.

[0056] In addition to the overflow downdraw method, the glass sheet can also be formed by, for example, a downdraw method (such as a slot down method) or a float method.

[0057] In the alkali-free glass plate of the present invention, the plate thickness is not particularly limited, but is preferably less than 0.7 mm, 0.6 mm or less, less than 0.6 mm, and particularly preferably 0.5 mm or less. The thinner the plate thickness, the lighter the organic EL device can be. The plate thickness can be adjusted by the flow rate and plate drawing speed during glass production.

[0058] The alkali-free glass plate of the present invention is preferably used as a substrate for an organic EL device, particularly a display panel for an organic EL television, or as a carrier for manufacturing an organic EL display panel. In the application of organic EL television, after a plurality of devices are produced on the glass plate, the glass plate is divided and cut into individual devices to reduce costs (so-called multi-panel cutting). The alkali-free glass plate of the present invention has a low liquidus temperature and a high liquidus viscosity, so that it is easy to form a large glass plate and can accurately meet such requirements. EXAMPLES

[0059] The present invention will be described below based on examples. Note that the following examples are merely illustrative and the present invention is not limited to the following examples.

[0060] Table 1 shows examples of the present invention (samples No. 1 to 12). In the table, RO represents MgO+CaO+SrO+BaO. Although not shown in the table, the glass composition contains about 0.005 to 0.02 mol% Na2O as an inevitable impurity from the glass raw materials.

[0061] [Table 1]

[0062] First, a glass batch prepared by mixing glass raw materials to obtain the glass composition shown in the table was placed in a platinum crucible and melted at 1600 to 1650°C for 24 hours. When melting the glass batch, a platinum stirrer was used to stir and homogenize the glass. Next, the molten glass was poured onto a carbon plate and formed into a plate shape, and then slowly cooled for 30 minutes at a temperature near the annealing point. The average thermal expansion coefficient CTE, density, Young's modulus, strain point Ps, annealing point Ta, softening point Ts, and high-temperature viscosity 10 in the temperature range of 30 to 380°C were measured for each sample. 4 Temperature in dPa·s, high temperature viscosity 10 3 Temperature in dPa·s, high temperature viscosity 10 2.5 Temperature in dPa s, liquidus temperature TL, and viscosity at liquidus temperature TL log 10 ηTL was evaluated.

[0063] The average coefficient of thermal expansion CTE in the temperature range of 30 to 380° C. is a value measured with a dilatometer.

[0064] The density is a value measured by the well-known Archimedes method.

[0065] The Young's modulus refers to a value measured by the well-known resonance method.

[0066] The strain point Ps, annealing point Ta, and softening point Ts are values ​​measured based on the methods of ASTM C336 and C338.

[0067] High temperature viscosity 10 4 dPa·s, 10 3 dPa·s, 10 2.5 The temperature in dPa·s was measured by the platinum sphere pulling method.

[0068] The liquidus temperature TL is the temperature at which crystals precipitate when a glass powder that passes through a standard sieve of 30 mesh (500 μm) and remains on a 50 mesh (300 μm) is placed in a platinum boat and held in a temperature gradient furnace for 24 hours.

[0069] liquidus viscosity log 10 ηTL is the viscosity of the glass at the liquidus temperature TL measured by the platinum ball pull-up method.

[0070] As is clear from Table 1, Samples No. 1 to No. 12 do not contain alkali metal oxides in the glass composition, and have a Young's modulus of 84 GPa or more, a strain point of 740°C or more, and a liquidus temperature of 1285°C or less, so that they are highly productive, can reduce thermal shrinkage in the LTPS process, and are unlikely to suffer from defects due to bending even when made larger and thinner. Thus, Samples No. 1 to No. 12 are suitable for use as substrates for organic EL devices. [Industrial Applicability]

[0071] The alkali-free glass plate of the present invention is suitable as a substrate for an organic EL device, particularly a display panel for an organic EL television, and a carrier for the production of an organic EL display panel. In addition, the glass plate is also suitable as a substrate for a flat panel display such as a liquid crystal display, a glass substrate for a magnetic recording medium, a cover glass for an image sensor such as a charge-coupled device (CCD) or a life-size proximity solid-state image sensor (CIS), a substrate and cover glass for a solar cell, a substrate for an organic EL lighting device, and the like.

Claims

1. The glass composition is, in mol%, SiO 2 64-71%, Al 2 O 3 13-17%, B 2 O 3 0-5%, Li 2 O+Na 2 O+K 2 O 0-0.5%, MgO 5-9%, CaO 4-10%, SrO 0-7%, BaO 1-7%, MgO+CaO+SrO+BaO 14-20%, and molar ratio Al 2 O 3 / BaO is 1.8 to 10, molar ratio B 2 O 3 / (MgO+CaO+SrO+BaO) is 0 to 0.2, molar ratio (B 2 O 3 + MgO) / SiO 2 is 0.1 to 0.15, molar ratio B 2 O 3 1. An alkali-free glass plate having a Young's modulus of 83 GPa or more, a strain point of 740° C. or more, and a liquidus temperature of 1350° C. or less.

2. Furthermore, substantially As 2 O 3 , Sb 2 O 3 The alkali-free glass sheet according to claim 1, characterized in that it does not contain

3. Furthermore, SnO 2 The alkali-free glass plate according to claim 1 or 2, characterized in that it contains 0.001 to 1 mol % of

4. The average thermal expansion coefficient in the temperature range of 30 to 380°C is 30 x 10 -7 / ℃~50×10 -7 The alkali-free glass sheet according to any one of claims 1 to 3, characterized in that:

5. Liquidus viscosity is 10 4.0 The alkali-free glass sheet according to any one of claims 1 to 4, characterized in that it has a viscosity of dPa·s or more.

6. The alkali-free glass sheet according to any one of claims 1 to 5, which is used for an organic EL device.

Citation Information

Patent Citations

  • Alkali-free glass

    JP2012106919A

  • Alkali-free glass

    JP2012184146A

  • Glass substrate for liquid crystal lens

    JP2012236759A

  • Alkali-free glass

    US20120282450A1

  • Non-alkali glass substrate

    WO2014087971A1